Education and science: current trends - Bodrov A. G., Nikishina A. A., Novikov I. A., Novikov A. P., Surkova G. V., Petrova D. D., Samostroenko G. M., Shatokhina O. V., Cherkashin I. S., Kapustina N. V., Rustamova I. T., Savenkov D. L., Veselova N. I., Grigorian S. S., Milioshina N. A., Firsova I. A., Chibilyova V. P., Chibiliov A. A., Sagitova V. R., Borovkova V. A., Borovkova V. A., Shevtsov V. V., Efremov A. Y., Diakieva B. B., Averianova E. V., Belonovskaia I. D., Sorokina O. A., Rakhimova O. N., Emelianova E. V., Chereshneva I. E., Kokhanova L. A., Golovko S. B., Khokhrina I. S., Khachev M. M., Temmoeva S. A., Cherkasova O. A., Zakirov R. S., Belousova rimma iurevna R. I., Novoselova A. N., Podoplelova N. M., Danilchenko S. L., Boldyrikhina V. N. (Education and science: current trends, 2018)
in the modern context complex, stable and balanced development of the region is possible only with the presence of developed and effectively implemented regional investment policy. In this regard, there is a need for the continuous development of scientific, methodological and practical aspects of the effective formation and implementation of RIPs, the search for methods and mechanisms for attracting investment resources to the regional economy, and ensuring a favorable investment climate. The research involves general methods for studying: observation, comparison, comprehensiveness, consistency, analysis, synthesis, as well as modeling and logical approach. The study clarified the concept of “regional investment policy” and its content, identified RIP types, identified the goal, objectives and principles of RIP development and implementation, proposed a model of RIP development and implementation, disclosed factors and problems of RIP formation and implementation, improved efficiency measures process of formation and implementation of the RIP. Application of the presented approach and model makes it possible to increase the efficiency of the development and implementation of the RIP, to ensure the region’s high competitiveness, stability, security, and improved adaptation to changing conditions.
Keywords: управление; регион; инвестиции; Management; политика; региональная инвестиционная политика; процесс разработки региональной инвестиционной политики; процесс реализации региональной инвестиционной политики; инвестиционная деятельность; региональное развитие; investments; policy; region; regional investment policy; process of regional investment policy implementation; investment activities; regional development